Development of squamous cell carcinoma into basal cell carcinoma under treatment with Vismodegib. (1st July 2014) - Saintes, C.; Saint‐Jean, M.; Brocard, A.; Peuvrel, L.; Renaut, J.J.; Khammari, A.; Quéreux, G.; Dréno, B.
Abstract: Background: Basal cell carcinoma (BCC) is the most common cancer in humans. Vismodegib, a Hedgehog pathway inhibitor, has proved its effectiveness in treating non‐resectable advanced BCC. Aim: However, its action on squamous cell carcinoma (SCC) is unknown. We present three SCC cases developed into BCC in vismodegib‐treated patients. Material and methods: We have described three cases of patients developing SCC during treatment by vismodegib for BCC. Results: Patient 1 was treated with vismodegib for five facial BCC. Due to the progression of one of the lesions at month 3 (M3), a biopsy was performed and showed SCC. Patient 2 was treated with vismodegib for a large facial BCC. A biopsy was performed at M2 on a BCC area not responding to treatment and showed SCC. Patient 3 was treated with vismodegib for a BCC on the nose. Due to vismodegib ineffectiveness, a biopsy was performed and showed SCC. Discussion: Two similar cases have been described in the literature. This could be due to the appearance of the squamous contingent of a metatypical BCC or to the squamous differentiation of stem cells through inhibition of the hedgehog pathway. Conclusion: In practice, any dissociated response of a BCC to vismodegib should be biopsied.